Prevalence of antibiotic-resistant Gram-negative bacteria having extended-spectrum β-lactamase phenotypes in polluted irrigation-purpose wastewaters from Indian agro-ecosystems - Avatsingh, Achhada Ujalkaur; Sharma, Shilpa; Kour, Shilippreet; Arora, Yukta; Sharma, Sheetal; Joshi, Divya; Chaudhary, Prem Prashant; Perveen, Kahkashan; Kamal, Mohab Amin; Singh, Nasib (Frontiers in Microbiology, 2023)
Antibiotic resistance in bacteria has emerged as a serious public health threat worldwide. Aquatic environments including irrigation-purpose wastewaters facilitate the emergence and transmission of antibiotic-resistant bacteria and antibiotic resistance genes leading to detrimental effects on human health and environment sustainability. Considering the paramount threat of ever-increasing antibiotic resistance to human health there is an urgent need for continuous environmental monitoring of antibiotic-resistant bacteria and antibiotic resistance genes in wastewater being used for irrigation in Indian agro-ecosystems. In this study, the prevalence of antibiotic resistance in Gram-negative bacteria isolated from irrigation-purpose wastewater samples from Sirmaur and Solan districts of Himachal Pradesh was determined. Bacterial isolates of genera Escherichia, Enterobacter, Hafnia, Shigella, Citrobacter, and Klebsiella obtained from 11 different geographical locations were found to exhibit resistance against ampicillin, amoxyclav, cefotaxime, co-trimoxazole, tobramycin, cefpodoxime and ceftazidime. However, all the isolates were sensitive to aminoglycoside antibiotic gentamicin. Enterobacter spp. and E. coli showed predominance among all the isolates. Multidrug-resistance phenotype was observed with isolate AUK-06 (Enterobacter sp.) which exhibited resistant to five antibiotics. Isolate AUK-02 and AUK-09, both E. coli strains showed resistant phenotypes to four antibiotics each. Phenotypic detection revealed that six isolates were positive for extended-spectrum β-lactamases which includes two isolates from Enterobacter spp. and E. coli each and one each from Shigella sp. and Citrobacter sp.Overall, the findings revealed the occurrence of antibiotic resistant and ESBL-positive bacterial isolates in wastewaters utilized for irrigation purpose in the study area and necessitate continuous monitoring and precautionary interventions. The outcomes of the study would be of significant clinical, epidemiological, and agro-environmental importance in designing effective wastewater management and environmental pollution control strategies.